Sinergi Dan Optimalisasi Green Banking Perbankan Syariah Dalam Mewujudkan Suistainable Finance - Rahmayati Nasution (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2018)
This study aims to find out how the responsibility of sharia banking in the implementation of Green Banking in the policy of financing distribution to customers, and synergy and optimization in realizing suistainable finance. This type of research uses the System Thinking Approach. Research data is secondary data obtained from literature data that support and obtained from website ojk.Teknik Modeling done to produce a model structure formulation that resembles the nature and behavior of complex real world system. The result of the research that green banking is an effort to change the paradigm in sharia bank development can be responsible through the way of financing to play a role in preventing environmental destruction.